Alternative splicing of a multi-drug transporter from Pseudoperonospora cubensis generates an RXLR effector protein that elicits a rapid cell death. - Elizabeth A Savory (Public Library of Science (PLoS), 2012)
Pseudoperonospora cubensis, an obligate oomycete pathogen, is the causal agent of cucurbit downy mildew, a foliar disease of global economic importance. Similar to other oomycete plant pathogens, Ps. cubensis has a suite of RXLR and RXLR-like effector proteins, which likely function as virulence or avirulence determinants during the course of host infection. Using in silico analyses, we identified 271 candidate effector proteins within the Ps. cubensis genome with variable RXLR motifs. In extending this analysis, we present the functional characterization of one Ps. cubensis effector protein, RXLR protein 1 (PscRXLR1), and its closest Phytophthora infestans ortholog, PITG_17484, a member of the Drug/Metabolite Transporter (DMT) superfamily. To assess if such effector-non-effector pairs are common among oomycete plant pathogens, we examined the relationship(s) among putative ortholog pairs in Ps. cubensis and P. infestans. Of 271 predicted Ps. cubensis effector proteins, only 109 (41%) had a putative ortholog in P. infestans and evolutionary rate analysis of these orthologs shows that they are evolving significantly faster than most other genes. We found that PscRXLR1 was up-regulated during the early stages of infection of plants, and, moreover, that heterologous expression of PscRXLR1 in Nicotiana benthamiana elicits a rapid necrosis. More interestingly, we also demonstrate that PscRXLR1 arises as a product of alternative splicing, making this the first example of an alternative splicing event in plant pathogenic oomycetes transforming a non-effector gene to a functional effector protein. Taken together, these data suggest a role for PscRXLR1 in pathogenicity, and, in total, our data provide a basis for comparative analysis of candidate effector proteins and their non-effector orthologs as a means of understanding function and evolutionary history of pathogen effectors.